Propinquity Of Avariciousness With Impulse Buying Tendency - Shivang Dwivedi, Ramesh Kumar Chaturvedi (International Journal of Advanced Science and Technology, 2020)
Impulse buying behavior is a sudden spontaneous urge of the consumer to make unplanned purchase after seeing the product in the retail space. Such type of behavior involves purchasing without much thinking. A number of studies have been conducted in the past regarding consumer decision making. This study has its base in the form of price sensitive impulse buyers. Though impulse buying behaviors has been studied in past, little evidence is available in literature on segmenting impulse buyer market; neither any specific scale has been developedto segment personalities based their impulse buying tendencies.Different personality traits from perspective of retail consumers are discussed and it is analyzed that how impulse buying market can be segmented based on the personalities of consumers. Using the technique of K means clustering analysis three segments are identified within impulse buying market having distinctive characteristics, among them avaricious value seeking impulse buyers segment dominates.Indian economy is a mixed economy and the Indian consumers generally tend to look for purchasing whenever the prices are low or at least the prices are fair which is eventually visible in this study also. This research will open insights about the segmenting impulse buyers to enable store managers enhance value per customer.